Assessment of the impact of malaria on CD4+ T Cells and haemoglobin levels of HIV-malaria co-infected patients - Daniel Nii Aryee Tagoe; Joseph Boachie (Journal of Infection in Developing Countries)
Introduction: The human immunodeficiency virus (HIV) and malaria destroy important cells required for proper immunological and haematological functioning of the body. This research therefore aimed to assess the effect of malaria on CD4+ and haemoglobin (Hb) levels of HIV-malaria co-infected patients.